2015
DOI: 10.1158/2326-6066.cir-14-0171
|View full text |Cite
|
Sign up to set email alerts
|

Antibody Blockade of Semaphorin 4D Promotes Immune Infiltration into Tumor and Enhances Response to Other Immunomodulatory Therapies

Abstract: Semaphorin 4D (SEMA4D, CD100) and its receptor plexin-B1 (PLXNB1) are broadly expressed in murine and human tumors, and their expression has been shown to correlate with invasive disease in several human tumors. SEMA4D normally functions to regulate the motility and differentiation of multiple cell types, including those of the immune, vascular, and nervous systems. In the setting of cancer, SEMA4D-PLXNB1 interactions have been reported to affect vascular stabilization and transactivation of ERBB2, but effects… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
87
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 94 publications
(94 citation statements)
references
References 49 publications
6
87
1
Order By: Relevance
“…They are also in good agreement with a recent report showing that Sema4D modulates the inflammatory cytokine milieu in a murine colon and mammary carcinoma model (48). Several clinical trials showed that advanced cancers can be controlled by immunotherapy.…”
Section: Discussionsupporting
confidence: 92%
“…They are also in good agreement with a recent report showing that Sema4D modulates the inflammatory cytokine milieu in a murine colon and mammary carcinoma model (48). Several clinical trials showed that advanced cancers can be controlled by immunotherapy.…”
Section: Discussionsupporting
confidence: 92%
“…220 In a slightly different approach, Evans et al (from Vaccinex, Inc., Rochester, NY, USA) reported that semaphorin 4D (SEMA4D) expression at the tumor invasive margin facilitates pro-tumorigenic inflammation, and that combining anti-SEMA4D monoclonal antibodies (mAbs) with ICBs or cyclophosphamide promotes immunological rejection in murine colorectal carcinoma models. 221 Finally, Blake et al…”
Section: Recent Preclinical Developmentsmentioning
confidence: 99%
“…VX15/2503 (Vaccinex, Inc.) is a highly novel, immunomodulatory monoclonal antibody that speciically targets SEMA4D (CD100), a receptor and soluble protein from the semaphorin family known to be involved in immune modulation [67] and regulation of normal bone formation [68]. Initial interest in this monoclonal antibody was rooted in results indicating that immune cell-dependent interactions were in fact responsible for its antitumor activity [67].…”
Section: Semaphorinsmentioning
confidence: 99%
“…Initial interest in this monoclonal antibody was rooted in results indicating that immune cell-dependent interactions were in fact responsible for its antitumor activity [67]. Early preclinical studies have determined that high concentrations of SEMA4D are expressed at the invasive border of many human cancers and that this border restricts the antitumor cell iniltrate from efectively combating the growing tumor.…”
Section: Semaphorinsmentioning
confidence: 99%